Biochemical and molecular characterisation of a new alkaline trypsin from Liza aurata: Structural features explaining thermal stability. (1st April 2016) - Bkhairia, Intidhar; Ben Khaled, Hayet; Ktari, Naourez; Miled, Nabil; Nasri, Moncef; Ghorbel, Sofiane
Highlights: New alkaline trypsin of Liza aurata was purified and characterized. The enzyme optimal temperature was 50 °C, showing a good application in detergence. The ORF mature cDNA was cloned and sequenced, showing a sequence of 222 aa. A 3-D structure model was built using the structure of Salmo salar as template. The 3-D structure model explain why Liza aurata trypsin acts at high temperatures. Abstract: This study investigated the fine structure and biochemical characterization of trypsin from the viscera of Liza aurata . The purified enzyme displayed an apparent molecular weight of 23 kDa as determined by sodium dodecyl sulphate–polyaccrylamide gel electrophoresis (SDS–PAGE). The optimum pH and temperature for the proteolytic activity were 10.0 and 50 °C, respectively. Trypsin was strongly inhibited by serine protease inhibitor. The cDNA of the mature trypsin was cloned and sequenced. It encodes a protein of 222 amino acids, having only 86% of identity with its most homologous trypsin II of the Salmo salar . A phylogenic analysis showed that L. aurata trypsin (LAT) is close to fish enzymes. Given the high amino acid sequence homology between fish enzymes, a 3-D structure model was built using the structure of S. salar as a template. According to this model, structural features common with warm-active trypsins would explain why LAT acts at high temperatures, unlike cold adapted enzymes.